1994
DOI: 10.2307/2944712
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing Mass Support for Political and Economic Change in the Former USSR

Abstract: Using survey data collected in Russia, Ukraine, and Lithuanian in 1990–92, we reexamine findings reported by Finifter and Mickiewicz (1992). Our analysis indicates a significant link between political and economic reform orientations. Individuals who prefer political reforms of a democratic nature also favor a decreased role of the state in guaranteeing social well-being. In addition, our finding that better-educated Soviet and post-Soviet citizens are more likely than the less-well-educated to prefer individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(42 citation statements)
references
References 16 publications
0
39
1
2
Order By: Relevance
“…Pushing the argument one step further, some authors have argued that the desire for political freedom and democratic institutions does not arise until countries reach a certain degree of material comfort and market liberalization (Lipset, 1959;Miller et al, 1994Miller et al, , 1996. Hence, the argument goes, not only is it preferable to postpone democracy until advanced stages of a country's economic development, but this sequence also meets citizens' preferences.…”
Section: Introductionmentioning
confidence: 99%
“…Pushing the argument one step further, some authors have argued that the desire for political freedom and democratic institutions does not arise until countries reach a certain degree of material comfort and market liberalization (Lipset, 1959;Miller et al, 1994Miller et al, , 1996. Hence, the argument goes, not only is it preferable to postpone democracy until advanced stages of a country's economic development, but this sequence also meets citizens' preferences.…”
Section: Introductionmentioning
confidence: 99%
“…A series of investigations in the beginning of transformation in post-socialist countries has demonstrated that the support for democracy makes a very important contribution to the support for free-market reform (Duch, 1993;Miller, Hesli, Reisinger, 1994;Gibson, 1996). But in the further course of transit with a prevalence of traditional thinking of people the democracy became a symbol of total impoverishment and unsuccessful economic reforms.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies of public attitudes toward democracy in Russia often report that younger, more urbanized, male, better educated, and better off Russians are more inclined to support democratic norms (Finifter and Mickiewicz, 1990;Hahn, 1991;Miller, Hesli, and Reisinger, 1994;Brym, 1996;Miller, Reisinger, and Hesli, 1996;Bahry, Boaz, and Gordon, 1997;Kulberg and Zimmerman, 1999). If this applies to support for human rights norms, then even if overall support for a particular dimension is weak, there are grounds for optimism because those groups who are more politically active and influential are the strongest supporters.…”
Section: Weak Structuration: Correlates Of Abstract Views On Rightsmentioning
confidence: 99%